Best Friends Forever : Bink & Gollie #3 - DiCamillo, Kate; McGhee, Alison, 1960-; Fucile, Tony (Somerville, Mass. : Candlewick Press, 2013)
The friendship of tall Gollie and short Bink is tested by Gollie's queenly airs, a lack of pancakes, and their shared profile in a book of record holders.
Keywords: Friendship -- Fiction; Friendship -- Fiction; Humorous fiction; Humorous fiction